2019
DOI: 10.1186/s13047-019-0315-4
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of foot self‐care in older people: a qualitative focus‐group study

Abstract: BackgroundFoot health is an important aspect of general health, and it can be maintained and promoted through foot self-care. However, little is known about older people’s experiences of caring for their feet. The aim of this study was to gather knowledge about experiences of foot self-care from the perspective of healthy older people in order to improve their welfare and their management of foot health.MethodsA qualitative descriptive design with focus groups was used. Seventeen older people recruited from da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 53 publications
2
24
3
Order By: Relevance
“…Our study found that age was one of the predictor of foot self-care behavior. Our study is not in accordance with a recent study which showed that foot self-care behavior in elderly patients were poor since they have physical difficulties and inadequate knowledge [37]. This difference might be due to that in our study we exclude elderly patients who have any physical difficulties such as patients who have loss of vision and who are immobile.…”
Section: Discussioncontrasting
confidence: 86%
“…Our study found that age was one of the predictor of foot self-care behavior. Our study is not in accordance with a recent study which showed that foot self-care behavior in elderly patients were poor since they have physical difficulties and inadequate knowledge [37]. This difference might be due to that in our study we exclude elderly patients who have any physical difficulties such as patients who have loss of vision and who are immobile.…”
Section: Discussioncontrasting
confidence: 86%
“…There was no significant association between changes in knowledge and performance scores, indicating that time constraints affect the ability to learn various topics in a short time. Community-dwelling older people with foot problems must seek help [5,42]. Tinea pedis and tinea unguium are among the top five skin disorders in individuals aged ≥ 60 years [43].…”
Section: Discussionmentioning
confidence: 99%
“…Community-dwelling older people with foot problems must seek help [ 5 , 42 ]. Tinea pedis and tinea unguium are among the top five skin disorders in individuals aged ≥ 60 years [ 43 ].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study to consider the views and opinions of older people, from the UK and from Portugal, about a tailored home-based lower limb, ankle and foot exercise programme aimed at preventing falls. Only one recent study has explored older adults views of selffootcare practices, including exercise in general 41 . This study provides relevant feedback from end-users that can be built into a culturally suitable future intervention in Scotland and Portugal.…”
Section: Discussionmentioning
confidence: 99%